Female brown bears use areas with infanticide risk in a spatially confined population - Penteriani, Vincenzo; Zarzo-Arias, Alejandra; Delgado, María del Mar; Dalerum, Fredrick; Gurarie, Eliezer; Peón Torre, Paloma; Sánchez Corominas, Teresa; Vázquez, Víctor M.; Pablo Vázquez García; Ordiz, Andrés (Ursus, 2020)
Areas used by female brown bears (Ursus arctos) with cubs-of-the-year (hereafter, FCOY) during the first months after den exit are crucial for offspring survival, primarily because of the risk of infanticide by male bears. Therefore, FCOY may avoid areas frequented by adult males during the mating season. The main aim of this study was to identify landscape features (i.e., structure, composition, and human footprint) that may differentiate the habitat use of FCOY in the small bear population of the Cantabrian Mountains (northwestern Spain; 2001–2016) from (a) areas frequented by females with yearlings, because older cubs are at less risk of infanticide than cubs-of-the-year, and (b) bear mating areas (i.e., the riskiest areas for FCOY because of the presence of adult males). During the first months after den emergence (Apr–Jun), FCOY settled in the roughest areas of the Cantabrian Mountains at most spatial scales. This settlement pattern might represent a behavioral adaptation of FCOY to reduce the risk of encounters with males during the mating season. However, FCOY also settled in similar landscapes to those used by adult bears during the mating season, which may increase the likelihood of risky encounters. Indeed, we observed a spatial overlap between observed locations of FCOY and mating areas, which may help explain the high frequency of infanticide observed in the Cantabrian Mountains. We hypothesize that the need for both shelter and food in early spring may ‘trap’ FCOY in otherwise favorable areas that overlap with mating areas. This may occur predominately in small and confined bear populations, such as the one in the Cantabrian Mountains, where a restricted range and limited habitat availability might prevent FCOY from avoiding risky areas successfully. During this study, V.P. and A.O. were financially supported by the Excellence Project CGL2017-82782-P financed by the Spanish Ministry of Economy, Industry and Competitiveness (MINECO), the Agencia Estatal de Investigación (AEI) and the Fondo Europeo ...